Output and Investment for Exponential Growth in Consumption - Stone, Richard; Brown, J. A. C. (Review of Economic Studies, 1962)
Journal Article Output and Investment for Exponential Growth in Consumption Get access Richard Stone, Richard Stone Cambridge Search for other works by this author on: Oxford Academic Google Scholar J. A. C. Brown J. A. C. Brown Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 3, June 1962, Pages 241–245, https://doi.org/10.2307/2295960 Published: 01 June 1962